2018
DOI: 10.1037/hea0000620
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of marital, parent-child, and sibling conflict during pediatric cancer treatment.

Abstract: Implications for development of interventions that target at-risk family relationships are discussed. Identifying processes that predict between-family variability in trajectories of family relationships is an important next step, particularly for the marital relationship. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 48 publications
3
19
0
2
Order By: Relevance
“…These findings seem to indicate that caregiver‐youth dyads behave differently in response to the medical experience but ultimately return to typical patterns as time from diagnosis increases. Either way, the positive relationship pattern demonstrated by the high‐involved group, is congruent with other research, which found caregiver‐youth conflict to be low following diagnosis and treatment …”
Section: Discussionsupporting
confidence: 86%
“…These findings seem to indicate that caregiver‐youth dyads behave differently in response to the medical experience but ultimately return to typical patterns as time from diagnosis increases. Either way, the positive relationship pattern demonstrated by the high‐involved group, is congruent with other research, which found caregiver‐youth conflict to be low following diagnosis and treatment …”
Section: Discussionsupporting
confidence: 86%
“…The siblings explained that if they articulate their needs, they appear dissatisfied, ungrateful, or even ill mannered. In line with previous research, they changed their behaviour and mode of interacting with their parents, trying to be cooperative and nonconflicting …”
Section: Discussionsupporting
confidence: 76%
“…In line with previous research, they changed their behaviour and mode of interacting with their parents, trying to be cooperative and nonconflicting. 2,5,8,20,[36][37][38] This study demonstrates that the need for intervention is greater when severity of the three variables increases. In relation to this result, the review by Lang et al 20 concluded that siblings request more psychosocial support from services when they experience strong cancer-related emotions.…”
Section: Discussionmentioning
confidence: 64%
“…Nowotwór u dziecka radykalnie zmienia ich sytuację życiową [10]. Diagnoza tej niebezpiecznej choroby zagraża równowadze całego systemu rodzinnego [11]. Sytuacja trudna rodziców jest związana z obawami dotyczącymi zdrowia i życia dziecka, z komunikacją z jego zdrowym rodzeństwem, intensywnością własnych reakcji emocjonalnych rodziców, obawami co do przyszłości dziecka, pogorszeniem sytuacji finansowej, koniecznością porzucenia pracy zawodowej, jakością opieki szpitalnej oraz wieloma aspektami leczenia i jego skutkami ubocznymi [12][13][14][15][16][17][18].…”
Section: Wprowadzenieunclassified